Mean platelet volume predicts outcome in patients with asymptomatic carotid artery disease. (26th October 2013) - Mayer, Florian J.; Hoke, Matthias; Schillinger, Martin; Minar, Erich; Arbesú, Itziar; Koppensteiner, Renate; Mannhalter, Christine
Abstract Background and Objective Platelets play a pivotal role in atherothrombosis and are potentially involved in the pathogenesis of atherosclerosis. We investigated whether mean platelet volume (MPV) predicts clinical outcome and progression of atherosclerosis in patients with asymptomatic carotid artery disease. Methods We studied 1006 of 1268 prospectively collected consecutive patients with asymptomatic carotid atherosclerosis who were evaluated by duplex sonography. Patients were followed up clinically for the occurrence of a major adverse cardiovascular event (MACE), a composite of myocardial infarction, percutaneous coronary intervention, coronary artery bypass graft, stroke and death. Results During a median follow‐up of 3·1 years (interquartile range, 2·5–3·5), a total of 316 (31·5%) MACEs were recorded. Increased levels of MPV were significantly associated with increased risk of the occurrence of MACEs (adjusted hazard ratio [HR] for an increase in one standard deviation [SD] of MPV 1·22, confidence interval [CI] 1·05–1·35, P < 0·01). Patients with MPV levels above 11·8 femtolitre (= fifth quintile) had a significantly higher event rate (41·3% vs. 29·3%, P < 0·001) with an adjusted HR for MACEs of 1·65 (95% CI 1·26–2·16, P < 0·001) compared with patients with MPV levels in the first to fourth quintile. No significant association was found between baseline MPV levels with either baseline degree or progression during a 6‐month follow‐up of carotid stenosis. Conclusion Mean platelet volume was independently and significantly associated with adverse cardiovascular outcome in patients with asymptomatic carotid atherosclerosis.